Genome-wide meta-analysis in Japanese populations identifies novel variants at the TMC6–TMC8 and SIX3–SIX2 loci associated with HbA1c. Issue 1 (December 2017) - Hachiya, Tsuyoshi; Komaki, Shohei; Hasegawa, Yutaka; Ohmomo, Hideki; Tanno, Kozo; Hozawa, Atsushi; Tamiya, Gen; Yamamoto, Masayuki; Ogasawara, Kuniaki; Nakamura, Motoyuki; Hitomi, Jiro; Ishigaki, Yasushi; et al.
Abstract Glycated haemoglobin (HbA1c ) is widely used as a biomarker for the diagnosis of diabetes, for population-level screening, and for monitoring the glycaemic status during medical treatment. Although the heritability of HbA1c has been estimated at 55–75%, a much smaller proportion of phenotypic variance is explained by the HbA1c -associated variants identified so far. To search for novel loci influencing the HbA1c levels, we conducted a genome-wide meta-analysis of 2 non-diabetic Japanese populations (n = 7, 704 subjects in total). We identified 2 novel loci that achieved genome-wide significance:TMC6 –TMC8 (P = 5.3 × 10−20 ) andSIX3–SIX2 (P = 8.6 × 10−9 ). Data from the largest-scale European GWAS conducted for HbA1c supported an association between the novelTMC6–TMC8 locus and HbA1c (P = 2.7 × 10−3 ). The association analysis with glycated albumin and glycation gap conducted using our Japanese population indicated that theTMC6–TMC8 andSIX3–SIX2 loci may influence the HbA1c level through non-glycaemic and glycaemic pathways, respectively. In addition, the pathway-based analysis suggested that the linoleic acid metabolic and 14-3-3-mediated signalling pathways were associated with HbA1c . These findings provide novel insights into the molecular mechanisms that modulate the HbA1c level in non-diabetic subjects.